TRANSPORT OF THE COMMON CRAB (SCYLLA SERRATA) IN LIVING CONDITION - Vasudeo, R B; Kewalramani, H G (Indian Journal of Fisheries, 2015)
Storage and transport of live edible crustaceans, especially crabs and lobsters for marketing them at places distant from the fishing grounds, has been quite a recent development in the fishing industry. To perfect these methods of transport and to increase their longevity in captivity, investigations have been undertaken in several maritime countries. In the U.S.A., England and France, floating stores, such as barges and pools have been devised, having adjustments for circulation, aeration and temperature control of sea-water, wherein lobsters and crabs have been kept aUve for two to three months. Macleese and Wilder (1955) and Macleese (1956) first studied temperature, salinity and oxygen contents of sea-water under which lobsters live in natural conditions.